2022
DOI: 10.1007/s40123-022-00529-4
|View full text |Cite|
|
Sign up to set email alerts
|

Expert Consensus on the Use of the PRESERFLO™ MicroShunt Device in the Treatment of Glaucoma: A Modified Delphi Panel

Abstract: Introduction:The implantation of the PRE-SERFLO TM MicroShunt (PMS) device has been shown to significantly lower increased intraocular pressure (IOP) in patients with primary open-angle glaucoma (POAG). However, guidelines on best practice for patient selection and pre-/peri-/postoperative care management are lacking. The aim of this modified Delphi panel was to achieve expert consensus on the role of the PMS to treat patients with glaucoma in Europe. Methods: Twelve European glaucoma surgeons experienced with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The optimal MMC concentration in patients at risk for hypotony-related complications is still debated; some studies have shown an increased risk with a higher MMC concentration after trabeculectomy [ 31 , 32 ]. However, recent recommendations were not conclusive regarding the MMC concentration to use in PMS surgery and left the final decision to the surgeon’s own experience [ 5 ]. In our opinion, in PMS implantation, an intraluminal stent insertion might be preferable to a lower MMC concentration to avoid early hypotony.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal MMC concentration in patients at risk for hypotony-related complications is still debated; some studies have shown an increased risk with a higher MMC concentration after trabeculectomy [ 31 , 32 ]. However, recent recommendations were not conclusive regarding the MMC concentration to use in PMS surgery and left the final decision to the surgeon’s own experience [ 5 ]. In our opinion, in PMS implantation, an intraluminal stent insertion might be preferable to a lower MMC concentration to avoid early hypotony.…”
Section: Discussionmentioning
confidence: 99%
“…Preserflo MicroShunt (PMS) (Santen Inc., Miami, FL, USA) implantation with mitomycin C (MMC) is considered a safe and effective surgical procedure for glaucoma patients [ 1 , 2 , 3 , 4 , 5 ]. However, postoperative complications may develop, leading to prolonged recovery and surgical failure in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…As the PMS remains a relatively novel device to treat patients with glaucoma, key guidance and optimal approaches to its use are primarily guided by the real-world experience of surgeons. This modified Delphi panel successfully built on the results of the previous Delphi panel [ 11 ], achieving consensus from a group of glaucoma surgeons with extensive experience of the PMS to provide further detailed guidance on the use of the device to treat patients with glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…This study followed the methodology of the 2021 Delphi panel [ 11 ], consisting of 3 questionnaire rounds and a virtual consensus meeting held following Round 2 of the Delphi panel. The virtual consensus meeting enabled discussion among panellists regarding statements that had not yet reached consensus and provided additional context for statements that had already reached consensus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation